Personal brands : manage your life with talent and turn it into a unique experience - Alvarez del Blanco, Roberto (Palgrave Macmillan, 2010)
The personal brand, like commercial brands, can become a means of affirming identity, highlighting ability and establishing reputation. Successful, stand-out people build their personal brand and make it count in their professional and personal lives. This book shows how to build and manage your personal brand